2021
DOI: 10.1016/j.mayocpiqo.2021.03.008
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Current Tobacco Status With Pain and Symptom Severity in Fibromyalgia Patients

Abstract: Objective: To describe current tobacco use among patients with newly confirmed fibromyalgia and evaluate the association between tobacco use status and severity of reported pain and other fibromyalgia symptoms.Patients and Methods: Participants in this study were adult patients (N¼1068) with fibromyalgia who met American College of Rheumatology 2010/2011 clinical criteria for fibromyalgia at the time of initial presentation to a Midwest fibromyalgia clinic (June 1, 2018, through May 31, 2019). Multiple linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…26,27 It may also provide insight for the association between tobacco use and hypersensitivity syndromes such as fibromyalgia. 28 Other than increasing opioid metabolism, smoking may also contribute to increased risk of OUD because it decreases tissue oxygenation, reduces fibroblast migration, and downregulates collagen synthesis and deposition. These changes prolong the healing process, thus providing an opportunity for prolonged opioid use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 It may also provide insight for the association between tobacco use and hypersensitivity syndromes such as fibromyalgia. 28 Other than increasing opioid metabolism, smoking may also contribute to increased risk of OUD because it decreases tissue oxygenation, reduces fibroblast migration, and downregulates collagen synthesis and deposition. These changes prolong the healing process, thus providing an opportunity for prolonged opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why smokers are more likely to require long-term opioid therapy and develop OUD than the general population 26,27 . It may also provide insight for the association between tobacco use and hypersensitivity syndromes such as fibromyalgia 28 . Other than increasing opioid metabolism, smoking may also contribute to increased risk of OUD because it decreases tissue oxygenation, reduces fibroblast migration, and downregulates collagen synthesis and deposition.…”
Section: Discussionmentioning
confidence: 99%
“… Pamuk et al (2009) and Lee et al (2011) found that smoking was associated with some psychological factors such as depression, anxiety, and fatigue in FM patients. Tobacco use has been associated with worse QoL in two studies that surveyed large samples of patients with FM ( Ge et al, 2019 ; Croghan et al, 2021 ). In this regard, it is important to highlight the research carried out by Zale et al (2014) , who found that patients with chronic pain view smoking as a way of coping with pain and even think that abstinence might interfere with pain management.…”
Section: Discussionmentioning
confidence: 99%
“…In this vein, physical activity in FM was positively related to brain responses generated during pain distraction, whereas sustained sedentary behavior was negatively associated with pain regulation ( Ellingson et al, 2012 ). In the other hand, in two recent studies ( Ge et al, 2019 ; Croghan et al, 2021 ) that surveyed large samples of patients with FM (668 and 1068, respectively), tobacco use was also associated with greater pain and other symptom severity, and with worse QoL.…”
Section: Introductionmentioning
confidence: 96%
“…The probable mechanisms explain that tobacco smoking affects cognitive function as due to extreme pain sensitization, it consumes the neurotransmitters, thus decreasing the neural resources needed for cognitive function [ 26 ]. Nicotine is indicated in causing derangements of neurotransmitters, including dopamine, serotonin, and noradrenaline, leading to defective pain modulation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%